The expression of immunohistochemical biomarkers PAX8 and CD117 in platinum resistant ovarian cancer at Saiful Anwar General Hospital, Malang, Indonesia - Widodo, Robby Rinaldi; Nurseta , Tatit; Mustofa, Edy; Arianto, Onni Dwi; Dewi, R. A. Rose Khasana (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Ovarian cancer, a prevalent gynecologic malignancy affecting women, poses a significant challenge due to the development of resistance to platinum-based therapy in its management. PAX8 and CD117 have demonstrated potential as predictive biomarkers for platinum resistance in ovarian cancer; however, studies exploring their immunohistochemical expression in relation to platinum resistance in ovarian cancer patients remain limited. This study aims to evaluate the immunohistochemical expression of CD117 and PAX8 in ovarian cancer tissues and investigate their association with the emergence of platinum resistance.   ABSTRACT Objective: Ovarian cancer, a prevalent gynecologic malignancy, frequently presents challenges due to platinum therapy resistance. This study aims to investigate a monitoring approach for post-operative ovarian carcinoma and evaluate the immunohistochemical expression of PAX8 and CD117 in ovarian cancer tissues, assessing their association with platinum resistance development. Materials and Methods: Employing a cross-sectional observational analytical design, this study utilized consecutive sampling of patients meeting predefined inclusion and exclusion criteria. Tissue samples, obtained from biopsy or surgical procedures and processed into representative paraffin blocks, underwent immunohistochemical analysis at the Anatomical Pathology Department of Saiful Anwar Hospital, Malang, Indonesia. Expressions of PAX8 and CD117 were evaluated using immunohistochemistry. Diagnostic performance was assessed through receiver operating characteristic (ROC) curves and Youden index calculations to determine sensitivity and specificity. Results: The study findings revealed that the area under the curve (AUC) for PAX8 and CD117 was 0.785 and 0.809, respectively. PAX8 expression exhibited a positive predictive value of 53.125%, negative predictive value of 87.50%, sensitivity of 18.75%, specificity of 51.85%, and accuracy of 60.0%. For CD117 expression, the corresponding values were 71.4%, 72.73%, 70%, 72.73%, and 70% for positive predictive value, negative predictive value, sensitivity, specificity, and accuracy, respectively. Conclusion: The immunohistochemical expression of PAX8 and CD117 in ovarian cancer tissues may serve as prognostic biomarkers for platinum resistance. Despite these findings, the study acknowledges several limitations that warrant refinement in future research.